Industrial transformation and shrimp aquaculture in Thailand and Vietnam: Pathways to ecological, social, and economic sustainability? - Lebel L. (2014)
Shrimp aquaculture in Vietnam is in the process of being transformed into a major industry around the intensification of the production system. The experiences of other countries in the region, especially in Thailand where high input production systems dominate, suggests that now is a critical time for intervention to redirect industry into pathways that are more sustainable ecologically, socially, and economically. In Thailand, years of experience with intensified systems and a complex industrial organization has not led to sustainable solutions. The challenge here is for society to regain control and then to redirect the transformation along more efficient and benign pathways. Our analyses suggest that current pathways in both countries are unlikely to lead to a sustainable industry. A complete transformation of the way shrimp are grown, fed, processed, distributed, and regulated is needed.